(3UajMI GdebfWQGJs ((3eMeO fhQi Hf eMehO Hf Cejf LdHi bUGH HGTi RGOg s)
(3ChdgG (B:s
(3GdebGdI GdChdi ai UajMI GdebfWQGJ hJTJed Ydi ebOeI hYTQI CHhGH GdaUd GdChd ai JSejI GdCTjGA GdehLhOI ai gPg GdBdI s
(3BNQgG (B:s
(3aeG hLOJg GWQM efg eG Hjf HUQc hGdCQV aGHb GdfSHI Edi ebjGS GdbWQ jMUd GdeWdhH HdG GQJjGH hGddg CYde hdjcf gPG BNQ GdcdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs